The Formulary System in the Republic of Kazakhstan in 2012–2014 - G. K. Zhussupova (Сеченовский вестник, 2016)
The formulary system is a drug supply management method promoting drugs with proved efficiency, safety and cost-effectiveness. It is a regulatory tool for effective, safe and economically feasible drug supply in the public health sector in many developed countries (the UK, the US and other) as well as in developing countries. The study objective is the analysis of the Formulary System in primary and secondary healthcare settings in 15 regions of the Republic of Kazakhstan in 2012–2014. The study involved a survey of healthcare institutions via e-mail with a unified questionnaire containing evaluation indicators. The collected data was aggregated in an Excel spreadsheet. The study findings showed the 3 year dynamics of the Formulary system in the Republic of Kazakhstan, though did not specify the causes of irrational drug use. Ключевые слова. Формулярная система, рациональное использование лекарственных средств, клиническая фармакология.